PTU-078 A prospective evaluation of adalimumab drug levels and anti-drug antibodies using two commercial elisa and the influence of 6-thioguanine nucleotides amongst patients with inflammatory bowel disease. (22nd June 2015) - Johnston, EL; Ward, MG; Warner, BD; Irving, PM
Abstract : Introduction: Some, 1, 2 but not all 3 studies have demonstrated a relationship between therapeutic drug monitoring (TDM) of adalimumab (ADA) and outcomes in inflammatory bowel disease (IBD). We evaluated the utility of TDM of ADA in patients with CD using two commercially available ELISA. Method: ADA drug levels (DL) and anti-drug antibodies (ADAb) were measured in CD patients (n = 80) from 2 tertiary referral centres, between November 13 and February 14 using the Lisa-Tracker Duo ((LT) Theradiag, France) and Immundiagnostik ELISA ((IM) Germany). Faecal calprotectin (FC), C-reactive protein (CRP <5 mg/L remission) and clinical activity (Harvey Bradshaw Index, (HBI) <5 remission) were also recorded. LT kits were provided by Theradiag at no cost. Results: Neither assay showed a significant difference in ADA DL between remission and active disease (See table ). No significant differences in DL were observed in TDM performed at trough (day 13/14, n = 13) or at any other time in the treatment cycle, nor amongst those receiving ADA every other week compared to weekly. Thiopurine metabolites (TGN) were performed in 51/52 patients taking thiopurines, (median 302, IQR 242–411 pmol/8×10 8 ). There was no significant difference between DL and TGN according to TGN quartiles. ADAb were detected in 1 (1.3%) patient using LT and 4 (5%) using IM. Concomitant immunomodulation or a therapeutic TGN (>235) did not significantly influence median DL or the detection of ADAb with either assay. IM ADA showed proportional positive bias (79.6%) against LT kit (Passing Bablok regression IM = 1.74 LT–0.06). Conclusion: No optimal cut-off could be identified that predicted clinical or biochemical remission or FC. Concomitant immunomodulation and TGN concentration was not associated with higher ADA DL. ADAb development was very rare whether measuring free (LT) or total (IM) ADAb. Further studies are needed to establish the cause of DL variation and understand differences in ADA pharmacokinetics in patients with CD. Disclosure of interest: E. Johnston: None Declared, M. Ward: None Declared, B. Warner: None Declared, P. Irving Speaker Bureau of: AbbVie, MSD, Takeda, Warner Chilcott, Shire, Ferring and Tillotts Pharma. References: Mazor Y, et al . Aliment Pharmacol Ther. 2014;40:620–628 Roblin X, et al . Clin Gastro Hepatol. 2014;12:80–84 Chiu Y, et al . Inflamm Bowel Dis. 2013;19:1112–1122